18 Subclinical myocardial inflammation in adults with type 2 diabetes: a clinical study using myocardial T2 mapping. (1st November 2021) - Ramesh, Pranav; Yeo, Jian L; Gulsin, Gaurav S; McCann, Gerry P
Abstract : Background: Chronic hyperglycaemia in Type 2 diabetes (T2D) results in a systemic low-grade inflammatory state. Inflammation is a key instigator in the development of heart failure in T2D. Cardiovascular magnetic resonance (CMR) T2 mapping is a technique which identifies myocardial oedema. The utility of T2 mapping to identify subclinical oedema as a marker of inflammation in T2D is unknown. We hypothesise that T2 times will be higher in subjects with T2D. Methods: CMR imaging on a 3-Tesla scanner was performed on 182 participants who were free of symptomatic cardiovascular disease. T2 images were acquired using the Siemens MyoMap sequence at the mid-ventricular short-axis slice. Twenty participants underwent a repeat CMR scan within two weeks to assess the test-retest reproducibility of T2. Intraclass correlation coefficient (ICC) and Bland-Altman plots were generated to assess reproducibility. T2 values between groups were compared using T-test or Mann-Whitney test as appropriate. Clinical determinants of T2 in T2D were assessed using multivariable linear regression. Results: 124 T2D (mean age 64±7, 66% male) and 40 controls (mean age 61±8, 60% male) were analysed. T2 times exhibited excellent intra-observer (ICC 0.98–0.99), moderate inter-observer (ICC 0.48–0.99), and poor test-retest variability (ICC 0.33–0.90). T2 times were significantly lower in subjects with T2D compared to controls (39.0±2.2 ms versus 40.1±2.9 ms, P=0.013). Stratification by sex revealed significantly lower T2 in females with T2D (39.4±2.4 ms versus 41.7±3.1 ms, P=0.003), but not in males, when compared to controls. Following multivariable adjustment, T2 time was positively associated with a non-white ethnicity (β=0.245, P=0.007) and diabetic duration (β=0.197, P=0.03) and inversely associated with systolic blood pressure (β= −0.215, P=0.018). Conclusions: T2 mapping has moderate-excellent observer variability but poor test-retest reproducibility in a cohort T2D. Lower T2 times in T2D may reflect early myocardial fibrosis but does not provide evidence of subclinical myocardial oedema and therefore is not able to detect low-grade myocardial inflammation.